Photosynthetic sulfide oxidation by Chloroflexus aurantiacus, a filamentous, photosynthetic, gliding bacterium. - Madigan, M T (1975)
Chloroflexus, a newly described genus of filamentous, photosynthetic, gliding bacteria, oxidizes sulfide anaerobically under photoautotrophic or photoheterotrophic growh conditions and deposits elemental sulfur outside the cell. The formation of sulfur granules outside the cell supports the idea that this organism is related to the green sulfur bacteria (Chlorobiaceae).